RETRACTED: The Role of Allograft Inflammatory Factor-1 in the Effects of Experimental Diabetes on B Cell Functions in the Heart - Sarkar, Amrita; Shukla, Sanket K.; Alqatawni, Aseel; Kumar, Anil; Addya, Sankar; Tsygankov, Alexander Y.; Rafiq, Khadija (Frontiers in Cardiovascular Medicine, 2018)
Diabetes mellitus (DM) often causes chronic inflammation, hypertrophy, apoptosis and fibrosis in the heart and subsequently leads to myocardial remodeling, deteriorated cardiac function and heart failure. However, the etiology of the cardiac disease is unknown. Therefore, we assessed the gene expression in the left ventricle of diabetic and non-diabetic mice using Affymetrix microarray analysis. Allograft inflammatory factor-1 (AIF-1), one of the top downregulated B cell inflammatory genes, is associated with B cell functions in inflammatory responses. Real-time reverse transcriptase-polymerase chain reaction confirmed the Affymetrix data. The expression of CD19 and AIF-1 were downregulated in diabetic hearts as compared to control hearts. Using in vitro migration assay, we showed for the first time that AIF-1 is responsible for B cell migration as B cells migrated to GFP-AIF-1-transfected H9C2 cells compared to empty vector-transfected cells. Interestingly, overexpression of AIF-1 in diabetic mice prevented streptozotocin-induced cardiac dysfunction, inflammation and promoted B cell homing into the heart. Our results suggest that AIF-1 downregulation inhibited B cell homing into diabetic hearts, thus promoting inflammation that leads to the development of diabetic cardiomyopathy, and that overexpression of AIF-1 could be a novel treatment for this condition.